Vitamin D endocrine system: basics - Norman, Anthony (Henry Stewart Talks, 2007)
What is a vitamin?, What is a hormone?, Vitamin D biology fundamentals, Calcium homeostasis, Classical biological actions of vitamin D, Vitamin D and endocrine system, Key discoveries in the field, Kidney as an endocrine gland for hormone-D, Vitamin D receptor, VDR target organs, Introduction to hormone D